Application for pinch design of heat exchanger networks by use of a computer code employing an improved problem algorithm table - Özkan, S; Dinçer, S (PERGAMON-ELSEVIER SCIENCE LTD, 2001)
In this work, the methods used in pinch design were applied to a heat exchanger network with the aid of an improved problem algorithm table. This table enables one to compose composite and grand composite curves in a simplified way. A user friendly computer code entitled DarboTEK, compiled by using Visual Basic 3.0, was developed for the design of integrated heat exchanger networks and estimation of related capital costs. Based on the data obtained from the TUPRAS petroleum refinery at Izmit, a retrofit design of heat exchanger networks was accomplished using DarboTEK. An investment of $ 3,576,627 is needed which will be paid back in 1.69 years simply by energy conservation due to heat integration. (C) 2001 Elsevier Science Ltd. All rights reserved.
Keywords: heat integration; pinch technology; retrofit design; computer program; Thermodynamics; Energy & Fuels; Mechanics